Assessing Bisphenol A (BPA) Induced Kidney Toxicity in Mammalian Model: A Comparative Study of Biometric, Histochemical, Histological and Behavioral Analyses - Faheem Nawaz; Asmat Ullah; Chaman Ara; Shumaila Zaifat; Muhammad Idnan; Madeeha Mehboob; Saira Azmet (RADS Journal of Biological Research & Applied Science, 2023)
Background: These BPA-containing plastics were commonly used to make toys, crockery and digital consumer products. The prime issue was the human exposure to BPA through food contamination from polycarbonate bottles and cars etc.